Local X‐ray magnetic circular dichroism study of Fe/Cu(111) using a tunneling smart tip. (27th January 2016) - DiLullo, Andrew; Shirato, Nozomi; Cummings, Marvin; Kersell, Heath; Chang, Hao; Rosenmann, Daniel; Miller, Dean; Freeland, John W.; Hla, Saw-Wai; Rose, Volker
Abstract : A tunneling smart tip of a synchrotron X‐ray scanning tunneling microscope provides simultaneously localized topographic, elemental and magnetic information. Abstract : Localized spectroscopy with simultaneous topographic, elemental and magnetic information is presented. A synchrotron X‐ray scanning tunneling microscope has been employed for the local study of the X‐ray magnetic circular dichroism at the Fe L 2, 3 ‐edges of a thin iron film grown on Cu(111). Polarization‐dependent X‐ray absorption spectra have been obtained through a tunneling smart tip that serves as a photoelectron detector. In contrast to conventional spin‐polarized scanning tunneling microscopy, X‐ray excitations provide magnetic contrast even with a non‐magnetic tip. Intensity variations in the photoexcited tip current point to chemical variations within a single magnetic Fe domain.